Performance of Broilers during Winter Season on Diet Supplemented with Black Cumin Seed Powder - Devi, N. Sushma; Vidyarthi, V. K.; Zuyie, R.; Rutsa, M. Catherine; Savino, N. (International Journal of Bio-resource and Stress Management, 2022)
A total of 120 Cobb-400 strains of broiler chicks were distributed into four treatments having five replications of six birds each. The birds in control group (Group 1) were offered standard broiler starter and finisher diets from 0–21 and 22–42 days of experiment, respectively. The birds of other three groups were also provided the same diets as in Group 1 along with black cumin seed powder @ 1.0% (Group 2), 2.0% (Group 3) and 3.0% (Group 4), respectively. Average values of body weight, gain in weight, feed intake and feed conversion efficiency did not differ significantly irrespective of the treatments. There was no mortality. Liveability was 100 % in all the groups. The values for performance index, haemoglobin, white blood cells, low density lipoprotein, high density lipoprotein and cholesterol was higher in group 3 than other groups. Dressing %, carcass weight and organs yield were higher in treated groups; red blood cells were unaffected; packed cell volume was higher in group 1; monocytes and basophils were nil. The values for heterophils and eosinophils were significant; however, lymphocytes count was unaffected. The value for net profit per kg weight gain of the broiler was highest in group 1. It can be concluded that dietary supplementation of 2.0% black cumin seed powder had shown better body weight, body weight gain, feed efficiency, performance index as well as haematological and biological constituents of the blood than control. So, supplementation of 2% black cumin powder in diet can be advocated.